Bahasa SMS dari Segi Grafologis, Sintaksis, dan Psikolinguistik - Yetty Morelent (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2011)
The widespread use of celular phones and SMS has spawned a variety of new word formation. These new words raise a language variety that leads to various interpretations. This is because the abbreviations and perpetuate sentences tend to "violate" graphological and syntactic rules, and the influence of psycholinguistics in the use of these abbreviations. This is because the creativity of the language community is very expressive and subjective regardless of the linguistic acceptability. The unacceptability is caused by the irregular shortenning of words. Keywords: SMS language, graphologist, syntax, psycholinguistics